Inovasi Biostimulan Nabati untuk Meningkatkan Ketahanan dan Produktivitas Padi - Fajri, Rahmatul; Fitriani , Fitriani; Al Fajar , Beni; Lestari , Ratna; Dwitya, Yonadiah; Jofrishal, Jofrishal (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Air Masin Village is a rice farming center currently facing serious challenges in sustainable production. Over the past five years, rice productivity has declined by 15%, allegedly due to the excessive use of synthetic fertilizers and pesticides. This practice has led to soil fertility degradation and increased pest resistance to chemical pesticides. In response to these issues, this community service program was designed to introduce locally sourced plant-based biostimulants as an environmentally friendly agricultural solution. Biostimulants have the potential to improve soil health, stimulate plant growth, and increase resilience to biotic and abiotic stress. This community service program aims to provide training to farmers in Air Masin Village on the techniques for producing and applying locally sourced plant-based biostimulants, thereby reducing dependence on synthetic chemical inputs. Furthermore, this program also aims to increase farmers' capacity in managing sustainable agricultural systems and open new business opportunities in the production and marketing of biostimulants. Several methods and stages of implementation were implemented, including identifying partner problems, activity outreach, training in the production of plant-based biostimulants, biostimulant effectiveness testing, farm management training, operational assistance, and finally, monitoring and evaluation. The training that has been implemented has had a positive impact on the local community, namely by changing mindsets and behavior regarding the importance of environmentally friendly agriculture.